MINUMAN FUNGSIONAL READY TO DRINK BERBAHAN BAKU REMPAH LOKAL - Mardiah, Mardiah; Noor, Rafiqa; Suprayatmi, Mira; Listianti, Elisa (Universitas Djuanda, 2019)
The purpose of this study was to study the extraction process of spices, obtain selected formulations based on organoleptic tests and physical stability tests. The research methodology is divided into two stages: the first stage is determining the composition of the spices (ginger, tamarind, turmeric, cardamom, lemongrass, cinnamon and cloves), using a one factor design that is the difference in the composition of the spices with 3 levels of treatment, namely (A1), (A2) and (A3) . The second stage uses the formula selected from the first stage and then is treated with 3 concentrations of spice extract (15%, 20% dan 25%) and the concentration of additional CMC (0%, 0.05% , 0.1% ). The results stated that the selected products were A3 composition spices (7.5% Curcuma xanthorrhiza extract, 25% tamarindus indica extract, 10% turmeric extract, 15% cardamom extract, 15% cinnamon extract, 15% lemongrass extract, 12.5% clove extract) with concentrations herbs 15% and CMC concentration 0.1%. This product was chosen because it was rated the most preferred. The results of physical stability analysis of selected products are quite stable with a sedimentation height of 0.04 cm on the 16th day. The selected product has a pH of 3.44, with a curcumin value of 13.70 ppm, and a total phenol of 31 ppm and an antioxidant of 2.97 ppm.